An Analysis of MSME’s Understanding and Implementation of SAK EMKM from the Banten Cultural Perspective - Faishal Rachman Wahid; Driana Leniwati; Muhammad Jihadi (GoAcademica Research & Publishing, 2026)
This study examines how prevailing cultural values and social norms in Serang City influence the understanding and implementation of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) among MSMEs. Employing a qualitative research design, this study utilizes thematic analysis to explore behavioral patterns underlying accounting practices. Data were collected through a combination of direct and indirect interviews with MSME actors. The findings reveal three dominant themes affecting SAK EMKM implementation: the prevalence of a practical mindset in financial decision-making, status quo bias accompanied by resistance to change, and information asymmetry coupled with limited mental investment in accounting learning. From a theoretical perspective, this research contributes to the accounting literature by extending the discussion on SAK EMKM implementation through a behavioral accounting framework grounded in a mental accounting approach. Practically, the findings underscore the importance of developing policy frameworks and accounting assistance programs that are contextualized, culturally sensitive, and aligned with the cognitive and behavioral characteristics of MSME actors. The novelty of this study lies in its cultural perspective on SAK EMKM implementation, offering behavioral insights that enrich conventional compliance-based accounting approaches.